Untopical Modernity in Neighbourhood Churches by Marcello Canino - Riccardo Serraglio (Histories of Postwar Architecture)
In the years of post-war reconstruction, the Italian authorities decided to expand the cities with suburban settlements for the lower classes. The popular neighborhoods had to include the essential social services, such as schools, sports facilities and parish centres. In particular, the law 18 December 1952 n. 2522 provided to allocate state funds to Italian dioceses for the construction of neighbourhood churches. For this reason, many architects and urban planners, including Marcello Canino, were commissioned to design types of ecclesiastical buildings suitables for the new popular districts. In a cultural milieu characterised by contrasts between tendencies prone to either tradition or modernity, Marcello Canino is distinguished among architects who were inspired by the past in the search for new types of ecclesiastical buildings. He was a professor of architectural design from 1930 to 1969 and Dean of the Faculty of Architecture of the University of Naples from 1943 to 1952. As an interpreter of an architectural renewal in the direction of a balance between the permanence of forms derived from classicism and the introduction of the constructive rationality of the Modern Movement, he produced some interesting projects for new neighbourhood churches. During the 1950s and ‘60s, he chose to revisit in a modern and personal key typologies and languages derived from the Italian architecture of the Medieval, Renaissance and Baroque periods. He interpreted the history of Italian architecture in the forms of a modern classicism, distant both from the present and from the past, defined untopical modernity by his disciple Michele Capobianco.